Consensus and update on the definition of on-treatment platelet reactivity to adenosine diphosphate associated with ischemia and bleeding - Tantry, Udaya S; Bonello, Laurent; Aradi, Daniel; Price, Matthew J; Jeong, Young-Hoon; Angiolillo, Dominick J; Stone, Gregg W; Curzen, Nick; Geisler, Tobias; Ten Berg, Jurrien; Kirtane, Ajay; Siller-Matula, Jolanta; et al. (Journal of the American College of Cardiology, 2013)
Dual antiplatelet therapy with aspirin and a P2Y12 receptor blocker is a key strategy to reduce platelet reactivity and to prevent thrombotic events in patients treated with percutaneous coronary intervention. In an earlier consensus document, we proposed cutoff values for high on-treatment platelet reactivity to adenosine diphosphate (ADP) associated with post-percutaneous coronary intervention ischemic events for various platelet function tests (PFTs). Updated American and European practice guidelines have issued a Class IIb recommendation for PFT to facilitate the choice of P2Y12 receptor inhibitor in selected high-risk patients treated with percutaneous coronary intervention, although routine testing is not recommended (Class III). Accumulated data from large studies underscore the importance of high on-treatment platelet reactivity to ADP as a prognostic risk factor. Recent prospective randomized trials of PFT did not demonstrate clinical benefit, thus questioning whether treatment modification based on the results of current PFT platforms can actually influence outcomes. However, there are major limitations associated with these randomized trials. In addition, recent data suggest that low on-treatment platelet reactivity to ADP is associated with a higher risk of bleeding. Therefore, a therapeutic window concept has been proposed for P2Y12 inhibitor therapy. In this updated consensus document, we review the available evidence addressing the relation of platelet reactivity to thrombotic and bleeding events. In addition, we propose cutoff values for high and low on-treatment platelet reactivity to ADP that might be used in future investigations of personalized antiplatelet therapy.